2006
DOI: 10.1007/s10157-006-0438-3
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase-2, matrix metalloproteinase-9, and tissue inhibitor of metalloproteinase-1 in the peripheral blood of patients with various glomerular diseases and their implication in pathogenetic lesions: study based on an enzyme-linked assay and immunohistochemical staining

Abstract: These results therefore suggest that MMP-2 plays an important role in the degradation of GBM, while MMP-9 only moderately affects the degradation of MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1
3

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 22 publications
0
18
1
3
Order By: Relevance
“…Diabetes affects ECM degradation, and activities of MMPs and TIMPs mostly regulate this process (27). Type IV collagenases, MMP-2 and -9, have been studied extensively in various glomerular diseases with conflicting results (10,14,26,27). However, in the present study, we found that both MMP-2 and -9 activities were increased significantly in diabetic kidney.…”
Section: Glomerular Tissue Levels Of Hcy and Nitric Oxide (No)contrasting
confidence: 42%
“…Diabetes affects ECM degradation, and activities of MMPs and TIMPs mostly regulate this process (27). Type IV collagenases, MMP-2 and -9, have been studied extensively in various glomerular diseases with conflicting results (10,14,26,27). However, in the present study, we found that both MMP-2 and -9 activities were increased significantly in diabetic kidney.…”
Section: Glomerular Tissue Levels Of Hcy and Nitric Oxide (No)contrasting
confidence: 42%
“…There is accumulating evidence that MMP-2 is involved in the development and progression of CKD and CVD by eliciting tissue remodeling via structural alterations in the glomerular and tubular areas as well as blood vessels [5,6,7,8]. Further, the plasma MMP-2 level is shown to be positively correlated with serum creatinine (Cr) levels in patients with CKD [9, 10]. In addition, Pawlak et al [11] have demonstrated that plasma MMP-2 but not MMP-9 significantly increased in hemodialysis patients and correlated with intima media thickness (IMT) levels.…”
Section: Introductionmentioning
confidence: 99%
“…[15,25] Many factors and markers can affect collagen remodeling in the glomerular basement membrane, including gelatinases and their inhibitory protein TIMP. [12][13][14]16,26] Elevated levels of biomarkers associated with matrix regulation in UTI were reported recently. Hatipoglu et al [27] measured the ratio of MMP9 to NGAL to Cr in children with symptomatic UTI, and compared them with asymptomatic patients with a contaminated urine exam, as well as with healthy children.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, the gelatinases (MMP2 and MMP9), in particular, have specific activity on type IV collagen, which is the main constituent of matrix. [15,16] The degradation of ECM is restrained by tissue inhibitors of metalloproteinases (TIMPs), which inhibit MMPs. Disruption of the balance between MMPs and their inhibitors may lead to fibrinogenesis and scar formation in the kidney.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation